PENDEKATAN PEMBELAJARAN PAI DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN - Rifqi Rohmatulloh; Bambang Samsul Arifin (Al-Mubin, 2023)
The Islamic religion is required to produce good ethical behavior for students, and educators are also required to organize students cognitively and effectively to prevent the transfer of knowledge outside the corridors of students and religion. This is proposed as a research problem to be applied in learning activities. The purpose of this study was to find out the various approaches from the perspective of educational psychology, approaches that are generally carried out and applied by educators, to generalize effective approaches to the educational process which in this case boils down to Islamic religious education. Educators, of course, in this case, get a value that is worth worship to be accountable for it apart from horizontally, namely vertically to Allah SWT. So that the learning approach to religious education, especially the Islamic religion, is felt to be very effective and efficient, namely the religious approach, because educators need and must master religious teachings through religious corridors. Islam prioritizes freedom of thought to obtain the widest possible knowledge with Islamic principles themselves so that minor corrections are made in learning